Expression of EGF and its receptor and histomorphometric analysis of epithelial tissue in gingival fibromatosis - Santos, Carolina de Oliveira; Silva, Thiago Fonseca; Bonan, Paulo Rogério; Guimaraes, André Luiz Sena; Coletta, Ricardo Della; Martelli-Júnior, Hercílio (Journal of Oral Diagnosis, 2016)
Gingival fibromatosis, a relatively rare condition, develops as a slowly progressing, benign, and localized or generalized enlargement of keratinized gingiva. The purpose of this study was to investigate the expression of epidermal growth factor and the epidermal growth factor receptor and perform histomorphometric analysis of epithelial tissue in gingival fibromatosis. Immunohistochemistry with antibodies against the aforementioned antigens was performed in gingival tissues from a family with hereditary gingival fibromatosis and a family with syndromic dental anomaly-associated gingival fibromatosis ; normal gingiva was used for comparison. The height of epithelial papillae and area and perimeter of epithelial layers were measured for histomorphometric analysis. Immunoreactivity to epidermal growth factor was found in the cytoplasm of epithelial cells, and immunopositivity for epidermal growth factor receptor was detected in the cytoplasm and membrane of epithelial cells. No differences in the expression of these proteins were observed among the groups. The gingival fibromatosis groups had higher epithelial papillae and larger epithelial areas that the normal gingiva group. Our findings suggest that enlargement of epithelial layers is associated with both forms of gingival fibromatosis.